Large long-range F-F indirect spin-spin coupling constants. Prediction of measurable F-F couplings over a few nanometers - Provasi, Patricio Federico (2004)
Large long-range indirect nuclear spin coupling constants are of great interest for quantum computers. But they are rarely observed and are usually considered very small, unless the coupled nuclear spins are proximate in space. Looking for counterexamples, we have calculated F−F couplings in four different series of acyclic hydrocarbons (alkanes, conjugated polyenes, conjugated polyynes, and cumulenes) where the coupled fluorine nuclei are separated by up to 11 bonds or 1.4 nm. The calculations were carried out at the level of the second-order polarization propagator approximation using locally dense basis sets. This approach has, in recent years, been shown to be particularly successful in reproducing indirect nuclear spin−spin couplings in organic molecules. We find that the F−F couplings in saturated alkanes diminish very quickly with the number of bonds between the coupled fluorine atoms, whereas in the conjugated polyenes and in particular polyynes the F−F couplings can be transmitted over much longer distances. We predict that the F−F coupling over 9 bonds or 1.1 nm is 12 Hz in (1E,3E,5E,7E)-1,8-difluoroocta-1,3,5,7-tetraene and the coupling over 11 bonds or 1.4 nm is 7 Hz in difluorodecapentayne. Analyzing the four Ramsey contributions, we find that the F−F couplings in the polyenes are dominated by the spin−dipolar term, which is known to be favored by π-electronic systems, whereas in the case of the polyynes the orbital paramagnetic terms make the largest contributions, although the spin−dipolar and the Fermi contact contributions are also significant.